OPTIMIZING FINANCIAL MANAGEMENT IN SMALL AND FAMILY-OWNED ENTERPRISES: A LITERATURE REVIEW ON SIGNALING AND AGENCY THEORIES - Setyawati, Amelia; Djoewita; Sugangga , Amelia; Restuningdiah, Nurika (Fakultas Ekonomi, Universitas Negeri Jakarta, 2024)
This research explores the role of ownership structure, agency relationship dynamics, and the implementation of financial signals in the context of small and family firm financial management. Employing the Systematic Literature Review method, a literature review was conducted to gather, filter, and analyze relevant literature on the topic. The research findings indicate that a deep understanding of ownership structure enables firms to design more efficient risk management policies and decision-making. Additionally, an understanding of agency relationship dynamics allows firms to manage conflicts of interest more effectively through the development of appropriate oversight mechanisms and incentives. The proper use of financial signals was also found to enhance transparency and external stakeholders' trust in the firm, thereby opening doors to better access to external capital. The conclusion drawn from this research is that effective financial management practices are crucial for the long-term success of small and family firms. The implications of these findings emphasize the need for firms to continuously update their knowledge and skills in financial management and actively apply proven principles in their own context. Thus, they can remain competitive in an ever-changing business environment and meet their long-term objectives.